Fuzzy Logic in Two Non-Interacting Tanks in Series - Abdullah Haji Abu Bakar, Abdullah (Universiti Teknologi Petronas, 2009)
Two Non-Interacting Tanks is commonly used in the petrochemical industry especially when it involves chemical reaction. Most chemical reaction needs optimum time to achieve the target conversion rate, so precise and controlled retention time of the chemicals in the tanks/reactors is very essential. This leads to the development of my project where I will compare fuzzy logic control, an advance control system and compare it with the conventional controller, which is the P1D controller. Fuzzy Controller is basically a controller that mimics a human in term of decision making by installing a range of human "decision" based on condition that we have introduced to the controller. PID Controller however is a controller based on the mathematical process modeling of the system & it will measure the error of the system from the set-point and perform a calculation for corrective action based on the PID equation. The results of the simulation will be compared based on the settling time, overshoot peak and maximum level at steady state of the tanks.